2013
DOI: 10.1158/1078-0432.ccr-12-2518
|View full text |Cite
|
Sign up to set email alerts
|

The Novel SMAC Mimetic Birinapant Exhibits Potent Activity against Human Melanoma Cells

Abstract: Purpose Inhibitor of apoptosis proteins (IAPs) promote cancer cell survival and confer resistance to therapy. We report on the ability of second mitochondria-derived activator of caspases (SMAC) mimetic, birinapant, which acts as antagonist to cIAP1 and cIAP2, to restore the sensitivity to apoptotic stimuli such as tumor necrosis factor (TNF)-α in melanomas Experimental Design Seventeen melanoma cell lines, representing five major genetic subgroups of cutaneous melanoma, were treated with birinapant as a sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 43 publications
9
79
1
Order By: Relevance
“…We further tested an additional Smac mimetic, birinapant, which was recently reported to induce efficient degradation of both cIAP1 and cIAP2. 28 Similar to BV6, birinapant also exhibited limited cIAP2 degradation in H1299 cells, and cIAP2 depletion, but not cIAP1 depletion, decreased H1299 cell viability upon TNFα and birinapant treatment ( Supplementary Figures S1a and b). Overall, these observations suggest that cIAP2 induction and stabilization by TNFα may inhibit Smac mimetic-induced apoptosis in certain cancer cell lines.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…We further tested an additional Smac mimetic, birinapant, which was recently reported to induce efficient degradation of both cIAP1 and cIAP2. 28 Similar to BV6, birinapant also exhibited limited cIAP2 degradation in H1299 cells, and cIAP2 depletion, but not cIAP1 depletion, decreased H1299 cell viability upon TNFα and birinapant treatment ( Supplementary Figures S1a and b). Overall, these observations suggest that cIAP2 induction and stabilization by TNFα may inhibit Smac mimetic-induced apoptosis in certain cancer cell lines.…”
Section: Resultsmentioning
confidence: 89%
“…25,26 While several studies have supported hypotheses for how cIAP2 survives in the presence of Smac mimetics, numerous independent studies have also shown that cIAP2 can be efficiently degraded by Smac mimetics in various cell lines. [27][28][29][30][31][32] These observations suggest the existence of other factors that specifically regulate cIAP2 stability upon Smac mimetic treatment. In this study, we propose a new mechanism involving USP11-mediated cIAP2 regulation.…”
mentioning
confidence: 88%
“…Mean and SEM of 17 individual CLL samples measured in duplicate or triplicate (samples no. 2,6,8,12,15,17,18,19,24,28,33,36,39,41,43,48,50) 2,6,8,12,15,17,18,19,24,28,33,36,39,41,43,48,50) are shown; *p < 0.05. several solid tumors, 16,35,36,[51][52][53] while another study showed that CLL cells remain resistant against Smac mimetics in the context of CD40 ligand stimulation. 39 Compared with CLL cells, BV6 showed little cytotoxicity against non-malignant B-cells, a finding also reported by other investigators in CLL.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Here, we found that TNF-a combined with the Smac-mimetic GT13072, an analog of TetraLogic's lead Smacmimetic drug birinapant (formerly TL32711), which is in phase 2 clinical trials and being developed for both solid tumors and hematologic malignancies as a single agent, 30 significantly induced cell death in Pkd1 null MEK cells ( Figure 2A) (P,0.001) and postnatal Pkd1 homozygous PN24 cells ( Figure 2B) (P,0.001). Importantly, Smac-mimetic plus TNF-a induced cell death in epithelial cells obtained from primary The effect of TNF-a (50 ng/ml) and/or Smac-mimetic (1 or 5 mM) on MEK cell viability.…”
Section: Tnf-a Exerts a Prosurvival Effect On Pkd1mentioning
confidence: 99%